PENINGKATAN PENINGKATAN KETERAMPILAN MENULIS TEKS CERAMAH MELALUI MODEL PEMBELAJARAN CONCEPT SENTENCE - Ramlan, Willyana; Mustika Sari TS, Shinta (STKIP Subang, 2019)
There were several reasons for conducting this study, students? seriousness in attending writing speech text were still low and not excited. Therefore, the teacher must choose and apply an effective teaching learning model to improve students? abilities in writing speech text. This study aims to improve students? abilities in writing speech text through concept sentence model and investigated students? responses through teaching writing speech text by using concept sentence model. The quasi experiment is the research method of this study. The control and experiment class were given pre-test and post-test to know the students? abilities before and after treatment. The questionnaire also used to gain the data about students? responses through teaching writing speech text by using concept sentence model. The research finding shows that the model concept sentence is effective to improve students? ability in writing speech text . The indicators of the success of by using SPSS 23.0 are that: (1) the mean of pre-test result in the experiment class was 64,18 and  post-test result in the experiment class was 81,28, meanwhile the mean of pre-test result in the control class was 60,57 and  post-test result in the control class was 71,50; (2) the students? responses through questionnaires found that the application concept sentence model was very positive.